БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИ БИЛИШ ФАОЛИЯТИНИ РИВОЖЛАНТИРИШНИНГ ПЕДАГОГИК – ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Tошева, Н.Т. (SCIENCE and SOCIETY, 2020)
The article deals with the opportunities to develop students’ cognitive activity in primary schools, the analysis of the process of developing this activity and to determine it’s main pedagogical directions.
Keywords: primary education; the process of sdudent`s cognition; pedagogical technologies; subject; the process of education; the opportunities of cognition; academic situation; didaktic approach; psychological approach; psychological-pedagogical peculiarities